Evaluation of water quality parameters, growth and proximate composition of juvenile crab, Portunus Pelagicus cultured in RAS and non RAS system - Shoyaib Kohinoor, S. M.; Arshad, Aziz; Sarker, S. M. Nurul Amin Harmuj Ali; Kamarudin, Mohd Salleh; Sulaiman, Muhammad Aliyu (Penerbit UKM, 2019)
This study aimed at evaluating the gut colonization by probiotics, the influence on the bacterial microflora, hematological profile, fish performance, rates body and proximate composition and water quality parameters in the cultivation of Nile tilapia juvenile of the Genetically Improved Farmed Tilapia (GIFT) strain. 1800 fry were randomly distributed into four experimental groups (T1 = basal diet (BD) without probiotic addition, T2 = BD + 0.5 % Bacillus cereus var. toyoi (BC), T3 = BD + 0.5% Bacillus subtilis C-3102 (BS); T4 = BD + 0.25 % BC + 0.25 % BS) with five replicates. Cages (0.175 m3) containing 90 tilapia fry (0.34 ± 0.06 g), were used as culture units and individually installed in 8.4 m3 ponds. Except for hemoglobin, hematocrit, glucose, and neutrophil levels, no differences in hematological profile were observed among the groups after 127 days of culture (P > 0.05). The probiotic bacteria either added individually or in combination, successfully colonized the intestines of the fish, without negatively influencing the intestinal bacterial microflora, growth rate, proximate composition, or water quality parameters (P > 0.05). Thus, dietary probiotic supplementation of juvenile Nile tilapia alters the hematological profile, especially hemoglobin, hematocrit, glucose, and neutrophil levels.